Crime, quarantine, and the U.S. coronavirus pandemic - Lopez, Ernesto (Criminology & public policy, 2021)
Priorresearch has produced varied results regarding the impact of the coronavirus pandemic on crime rates, depending on the offenses and time periods under investigation. The current study of weekly offense rates in large U.S. cities is based on a longer time period, a greater number of offenses than prior research, and a varying number of cities for each offense (max = 28, min = 13, md = 20). We find that weekly property crime and drug offense rates, averaged across the cities, fell during the pandemic. An exception is motor vehicle theft, which trended upward after pandemic-related population restrictions were instituted in March 2020. Robbery rates also declined immediately after the pandemic began. Average weekly homicide, aggravated assault, and gun assault rates did not exhibit statistically significant increases after March. Beginning in June 2020, however, significant increases in these offenses were detected, followed by declines in the late summer and fall. Fixed-effects regression analyses disclose significant decreases in aggravated assault, robbery, and larceny rates associated with reduced residential mobility during the pandemic. These results support the routine activity hypothesis that the dispersion of activity away from households increases crime rates. The results for the other offenses are less supportive.